Exploring the inter-connections between Alternative Agrifood and Seafood Networks for building food systems resilience - Kristen Lowitt; Charles Z. Levkoe; Sarah-Patricia Breen; Lindsay Harris; Hannah L. Harrison; Jon MacDonald; Phoebe Stephens; Joshua S. Stoll; Bruna Trevisan Negri; Connor Warne; Philip A. Loring (Canadian Food Studies)
In the context of intensifying threats to food systems and a growing need for resilience, Alternative Agrifood Networks (AANs) and Alternative Seafood Networks (ASNs) have emerged as notable bright spots across North America. Collectively, AANs and ASNs comprise Alternative Food Networks (AFNs) - the micro, small, and medium-sized enterprises which are important, but often overlooked, actors in food systems. However, a critical limitation for food system resilience is that agriculture and fisheries remain chronically siloed in research, legislation, regulation, and advocacy. In this field report, we explore the opportunities and challenges of linking ASNs and AANs to build more resilient food systems. To do so, we draw on our experiences as an interdisciplinary group of food systems researchers and practitioners that came together in 2022 through the Agrifish Resilience project. Based on a series of reflective collaborative conversations that we held as a team, we share our key insights for building resilience across agriculture and fisheries focusing on three main themes: the role of ASNs and AANs in food system resilience, our perspectives on what resilience in food systems means, and prospects for collaboratively building resilience. We conclude by proposing the idea of boundary objects as a way of bringing ASNs and AANs together, with some examples of what this looks like in practice, and the role for interdisciplinary teams like ours.